Novel STAT3 variant causing infantile-onset autoimmune disease - Pan, Miao; Kurtz, Justin (Frontiers in Medicine, 2023)
Signal transducer and activator of transcription 3 (STAT3) is a member of the STAT protein family implicated in the development of infantile-onset multisystem autoimmune disease. STAT3-related autoimmune disease is characterized by multiorgan autoimmunity, lymphoproliferative disease, and recurrent infections. The presentation is variable, with some patients also developing neonatal diabetes mellitus and interstitial lung disease. Gain-of-function variants in the Src homology 2 domain, leading to autophosphorylation and activation of STAT3, have been previously reported in patients with disease. Here, we report a patient with a novel missense variant, p.Glu616Ala, in STAT3 presenting with infantile-onset multisystem autoimmune disease.